Factors Influencing Consumer Buying Behaviour Through Facebook Live Streaming - Azizan, Anim Zalina; Chiew, Ai Theng (Research in Management of Technology and Business, 2023)
Due to the rise of online live streaming in recent years, many socializing platforms launched live streaming services one after another, which spurred the live streaming trend. The main objective of this study is to identify factors that drive consumer buying behavior in live streaming commerce. The problem issues in this study are aspects of trust, security, and privacy of the Facebook platform, unclear product information shared on Facebook platforms, and online fraud faced by consumers. The survey in this study targets 255 respondents. Data are collected using a questionnaire and quantitatively analyzed using SPSS software. To achieve the objectives, the researcher conducted a descriptive analysis. The results of the study show that there are 4 factors that promote consumer buying behavior in live streaming commerce, namely competitive price, consumer trust, presenter professionalism, and purchase intention, and the dominant factor that promotes consumer buying behavior is competitive price. The results of this study should provide valuable insights for all readers.